The Themes of Alienation and Homelessness in the Poetry of Nissim Ezekiel: A Critical Study - Vipin Kumar; Dr. Vivek Kumar Dwivedi (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2023)
Nissim Ezekiel, a renowned Indian English poet, is celebrated for his exploration of complex themes such as identity, existentialism, and human relationships. This study examines the themes of alienation and Homelessness, which refer to the estrangement of individuals from society, the self, or the environment, in Ezekiel’s poetry. Analyzing key poems such as “Night of the Scorpion,” “Enterprise,” “The Patriot,” “Background, Casually,” and “Poet, Lover, Birdwatcher,” this paper identifies four aspects of alienation present in his work: alienation from society, the self, the environment, and interpersonal relationships. In Ezekiel’s poetry, characters often experience a disconnect from their society due to factors such as cultural differences, social expectations, and spiritual disillusionment. His work also delves into the internal struggle of individuals trying to understand their own identities, resulting in a sense of alienation from the self. The theme of alienation from the environment is explored through the portrayal of hostile natural elements and the protagonists’ inability to find solace in their surroundings. Lastly, Ezekiel’s poetry examines the breakdown of interpersonal relationships, highlighting how feelings of estrangement can manifest within close connections. This study demonstrates that Ezekiel’s portrayal of alienation is a powerful reflection of the complex, multi-layered nature of human existence. His work serves as a reminder that the quest for belonging and connection is an ongoing struggle that transcends culture and geography. By examining the elements of alienation in his poetry, we gain a deeper understanding of Nissim Ezekiel’s perspective on human existence and the challenges that individuals face, ultimately fostering empathy and understanding among people from diverse backgrounds.